Live To Your Local Cinema - Barker, M. author. aut Link
VIII, 105 p.
Keywords: The digital broadcasting of performances to cinemas, or 'livecasting', burst onto the world scene in 2006. This book explores the reasons for its rise, examines the aesthetics of filming theatre and opera performances, and explores who the audiences are and what they want.